Effect of alternating current frequency on corrosion behavior of X80 pipeline steel in soil extract solution of Dagang. (January 2020) - Qin, Qingyu; Wei, Boxin; Bai, Yunlong; Nan, Li; Xu, Jin; Yu, Changkun; Sun, Cheng
Abstract: Effects of AC frequencies on corrosion behavior of X80 pipeline steel was investigated in soil-extract solution of Dagang using polarization curves, electrochemical impedance spectroscopy, weight-loss test and surface analysis techniques. Results show that the corrosion potential of X80 pipeline steel shift in the negative direction under the effect of AC. The maximum pitting depth and corrosion rate of the steel specimen decrease with the AC frequency increasing, and there is a function relationship, y = 45.63x −0.5, between the maximum pitting depth and the AC frequency. The alternating current just like an oxidant changes the component proportion of corrosion products rather than the types due to AC rectification. Highlights: Effect of AC frequency on corrosion of X80 steel has been investigated. AC current accelerates corrosion of X80 steel. Maximum pitting depth is a function of AC frequency. AC current as an oxidant increases percentage of products of high-valent iron. Rectification effect of AC current decreases with AC frequency increasing.